Issues on the application of component-oriented software development: Formulation of research areas - Aris H.; Salim S.S. (2023)
This research presents the outcomes of a study performed with the aim of identifying the issues affecting the application of Component-Oriented Software Development (COSD) amongst the software developers, which consist of those who use components in their software development and those who do not. The information required in the form of problems faced in using components, factors affecting the use of components and reasons for not using components in software development was obtained through questionnaires distribution amongst the software developers in Malaysia. The information gathered was used to determine the issues that affect the application of COSD. These issues are presented in a cause-effect diagram and categorised into technical, managerial and ethical. It serves as the basis for the derivation of a list of possible research areas that can be explored by the researchers in this field. Each research area is then linked to the issues that it solves. This is to ensure that the research area of choice will optimally contribute to the development of COSD in order to promote COSD application amongst the software developers. 2008 Asian Network for Scientific Information.